Re(de)construction of identity through social constructionism in selected novels by Podder, Beti, and James - Tay, Lai Kit; Subraman, Manimangai; Wan Yahya, Wan Roselezam (Scientific Publishing House, 2016)
Identity is an extremely complex and subjective theme to discuss – especially when it comes to setting a fixed definition. This article examines the construction of identity through the lens of social constructionism and draws in several working definitions from various sociologists to purport the core of this article. The sociological concept will be applied on three different texts: Escape from Harem by Tanushree Podder (2013); The Poor Christ of Bomba by Mongo Beti (1971); and The Book of Night Women by Marlon James (2009). Focusing only on the protagonist from each text, we attempt to carry out the analysis of this paper by looking at the flux of identity within them. We argue that identity is not a fixed and permanent state of a character; instead it is constructed by social, political, economic, and personal experience. All the three protagonists, Zeenat, Denis, and Lilith experience specific identity fluctuation in their lives. As such, we will be looking at the psychological growth and changes in each character and determine whether or not his/her sense of self is reconstructed or deconstructed at the end of their journey to self-discovery.